Synthesis of imidazo[1,2-a]-pyridine derivatives - Chien, Tran Van; Thien, Dao Duc; Loc, Tran Van; Sung, Tran Van (Vietnam Journal of Chemistry, 2014)
The synthesis of imidazo[1,2-a]-pyridine derivatives was carried out by subsequential reactions: condensation, substitution and reduction, using the commercially available 2-aminopyridine as starting material. Keywords: 2-aminopyridine, 2-chloroimidazo[1,2-a]-pyridine, 1,1’-carbonyldiimidazole.